Kesiapsiagaan Bencana pada Acara Internasional: Penguatan Kapasitas Kebencanaan terhadap Penyelenggaraan Balap F1 Powerboat Danau Toba, Indonesia - Supriyati, S; Irawan, Andri; Putra, Anggara Setyabawana; Susilastuti, S; Adiputra, Agung; Wibowo, Agus (Jagratara: Journal of Disaster Research, 2024)
Lake Toba is located on the Sumatran Fault, an active fault line that runs along the island of Sumatra. Therefore, Toba Regency is an area prone to earthquakes. The potential for earthquakes can also cause secondary hazards such as landslides. As one of the Super Priority Tourism Destinations (DPSP), the government is promoting the region through the Formula 1 (F1) Powerboat racing championship held from 2023 to 2027 to increase tourist visits to Lake Toba. The purpose of this study is to provide capacity-building recommendations for the organization of the F1 Powerboat in the Lake Toba Area. The F1 Powerboat is one of the prestigious international events held in the Lake Toba Area from 2023 to 2027. In 2024, this event will be participated in by 9 countries with a total of 18 racers. To anticipate panic due to disasters during the race, capacity building is needed to enhance disaster preparedness. The research methods used in this study include literature review and data collection, followed by data analysis to generate recommendations. Recommendations to improve disaster preparedness can be achieved by enhancing regional readiness to reduce disaster risks, developing planning, multi-stakeholder collaboration, understanding risks, disseminating information, training, simulations, providing safety and disaster preparedness facilities and infrastructure, and building a culture of disaster preparedness through safety briefings and disaster preparedness simulations.